IODINE METABOLISM AND PROPHYLAXIS OF IODINE DEFICIENT DISEASES IN CHILDREN AND ADOLESCENTS - E.A. Troshina; N.M. Platonova ("Paediatrician" Publishers LLC, 2008)
The main aspects of iodine metabolism in human organism, physiological need in this microelement, prevalence and criteria of diagnosis of iodine deficient diseases are presented in this article. The measures, essential to the iodine deficiency prophylaxis are described, and possible choices of compensation of iodine deficiency in provisions, including milk formulas, are discussed. recommendations of international expert medical societies, giving evidence of prophylaxis of thyroid gland diseases, related with iodine deficiency, are presented.Key words: children, iodine, prophylaxis.